2010
DOI: 10.1111/j.1464-410x.2010.09871.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of pathological reporting for renal cell cancer: implications for systemic therapy, prognostication and surveillance

Abstract: Study Type – Prognosis (retrospective cohort) Level of Evidence 2b What’s known on the subject? and What does the study add? Pathology reporting is an important aspect of cancer care for all solid malignancies and the College of American Pathologists has set forth specific guidelines. Many prognostic nomograms for kidney cancer rely on important pathologic characteristics but it is unknown if current reporting practices permit use of these models. This study shows limitations in the current pathological repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Unfortunately, while recommended by the College of American Pathologists and potentially useful in prognostication, less than half of nephrectomy pathology reports mention this feature. [21]…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, while recommended by the College of American Pathologists and potentially useful in prognostication, less than half of nephrectomy pathology reports mention this feature. [21]…”
Section: Discussionmentioning
confidence: 99%
“…1). Despite extensive efforts to standardize and educate SEER registry participants performing extraction/ coding, there are inherent issues with pathology assessment, especially in kidney cancer [3]. These are deficiencies that may not be overcome by registry efforts and rely, instead, on education by the pathology community on the essential elements in pathology reporting and current histologic classification.…”
Section: Discussionmentioning
confidence: 99%
“…Registry medical abstractors are also instructed to gather additional information from the medical records and operative reports. Although the College of American Pathology sets forth specific organ/cancer site guidelines for reporting, significant deficiencies in pathologic reporting exist [2,3]. SEER histology coding greatly depends on the pathologist, but currently, there is no method of pathologic data auditing.…”
Section: Introductionmentioning
confidence: 99%
“…Shuch et al reported that tumor classification was omitted in 28% of pathology reports, which may interfere with the selection of systemic therapy and enrollment into adjuvant clinical trials (33). Various terminologies have been and are being used, such as sarcomatoid differentiation, dedifferentiation (28), component, features, and progression.…”
Section: Pathology Reportingmentioning
confidence: 99%